Structure-Activity Relationship Analysis of YM155 for Inducing Selective Cell Death of Human Pluripotent Stem Cells - Go, Young-Hyun; Lim, Changjin; Jeong, Ho-Chang; Kwon, Ok-Seon; Chung, Sungkyun; Lee, Haeseung; Kim, Wankyu; Suh, Young-Ger; Son, Woo Sung; Lee, Mi-Ok; Cha, Hyuk-Jin; Kim, Seok-Ho (Frontiers in Chemistry, 2019)
Despite great potential for regenerative medicine, the high tumorigenic potential of human pluripotent stem cells (hPSCs) to form undesirable teratoma is an important technical hurdle preventing safe cell therapy. Various small molecules that induce the complete elimination of undifferentiated hPSCs, referred to as ‘stem-toxics’, have been developed to facilitate tumor-free cell therapy, including the Survivin inhibitor YM155. In the present work, based on the chemical structure of YM155, total 26 analogs were synthesized and tested for stem-toxic activity toward human embryonic stem cells (hESCs) and induced PSCs (iPSCs). We found that a hydrogen bond acceptor in the pyrazine ring of YM155 derivatives is critical for stem-toxic activity, which is completely lost in hESCs lacking SLC35F2 encoding a solute carrier protein. These results suggest that hydrogen bonding interactions between the nitrogens of the pyrazine ring and the SLC35F2 protein are critical for entry of YM155 into hPSCs, and hence stem-toxic activity.